ANALISIS ASPEK LINGKUNGAN, SUMBER DAYA MANUSIA, PEMASARAN PABRIK KARET PT. DARMA KALIMANTAN JAYA - Ismatul Aula; Ananda Rizki Aulia; Rina Widayanti; Mita Ananda; Muhammad Firliadi Noor Salim (CV. Denasya Smart Publisher, 2024)
This study aims to assess the performance of a rubber factory that has implemented good and environmentally friendly production practices. However, the factory faces serious challenges related to the uncertainty of raw material supply. In this study, we used a qualitative approach, collecting data through in-depth interviews with the deputy factory manager and direct observation of the ongoing operational processes. The results of the study indicate that the rubber factory has met the established environmental standards. Waste management is carried out in accordance with applicable regulations, thus making a positive contribution to environmental sustainability. However, the factory experiences difficulties in procuring raw materials due to price fluctuations and the impact of climate change, which in turn affects production capacity and marketing planning. The factory management has attempted to overcome these challenges by establishing strategic partnerships with local farmers and diversifying raw material sources. Recommendations from this study emphasize the importance of risk mitigation strategies related to raw material price fluctuations and increasing cooperation with various parties to ensure sustainable supply.